Pelatihan Tari Tanun Di SMA Negeri 1 Sawahlunto Pada Kegiatan Ekstrakurikuler Tari - Willy Tri Rama Putra; Yuliasma Yuliasma (SENDRATASIK UNP, 2020)
This is a qualitative research with a descriptive analysis method. The main instrument in this study was the researcher itself and was assisted by supporting instruments such as writing instruments and cameras. The data used were primary and secondary data. The data was collected through literature study, observation, documentation, and interview. The data analysis was conducted by reducing the data, modeling the data (data display), and taking / verifying conclusions. The results show that 1) extracurricular dance planning can be conducted well as expected, the material selection is in accordance with students’ needs and abilities, and the schedule selection has been determined by the principal and is always consistent in its implementation, 2) the implementation techniques taught to students give optimal quality such as doing varied warm-ups, teaching difficult to easy movements, and emphasizing parts of the motion by using words such as 1-2-Hentak-Turak, 5-6-Sorong-Turak, 3) students' abilities which looks very good consist of several parts, namely motion, rhythm, and expression. In terms of doing movements, the students are always consistent (there is no change). In terms of rhythm, the students are always good at doing movements because the trainer always provides varied counts and consistently provides rhythms with sound or music during warming up. In terms of expression, students are also spontaneous in doing movements and giving off a beautiful smile. This is due to the fact that the trainer always explains the meaning of motion in every movement the students do.